Pengaruh halal awareness, electronic word of mouth, dan brand trust terhadap keputusan pembelian kosmetik halal glad2glow pada mahasiswa muslim - Bunga Aulia Khafifa; Mukhammad Yazid Afandi; Muhamad Maimun (Journal of Halal Industry Studies, 2026)
The decision to purchase halal cosmetics among the younger generation is influenced by various religious, digital, and psychological factors; however, previous research findings have shown inconsistent results. This study aims to analyze the influence of halal awareness, electronic word of mouth (e-WOM), and brand trust on the decision to purchase Glad2Glow halal cosmetics among Muslim students at Sunan Kalijaga State Islamic University in Yogyakarta. The study employed a quantitative approach using a survey design involving 110 respondents selected through purposive sampling. Data were collected via a Likert-scale questionnaire and analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The results indicate that halal awareness and electronic word of mouth do not have a significant effect on purchasing decisions. Conversely, brand trust was found to have a positive and significant effect on purchasing decisions, indicating that trust in product quality, brand reputation, and halal certification are key considerations for consumers when making purchasing decisions. Collectively, these three variables explain 72.2% of the variation in purchasing decisions, while the remainder is influenced by other factors outside the research model. These findings confirm that, among Muslim college students, brand trust plays a more dominant role than halal awareness or information obtained through digital media in shaping purchasing decisions for halal cosmetics. The research results have implications for the development of marketing strategies in the halal cosmetics industry, with an emphasis on strengthening consumer trust in brands.